Teacher Competency Development Management in Mts Istiqlal Deli Tua Serdang Regency - Muhammad Irjaul Fuadi; Fatkhur Rohman (Universitas Muhammadiyah Enrekang, 2023)
Teacher development management is an effort that is carried out through activities, training and development of the abilities possessed by educators individually/groups to achieve the desired goals by managing teaching staff. The purpose of writing this research is to find out how the management of teacher competency development is at MTs Istiqlal Deli Tua. The method used in this research is using descriptive qualitative research method. The results of the study show that the Management of Teacher Competency Development at MTs Istiqlal Deli Tua includes three stages of activity namely planning, implementation/implementation and evaluation of teacher competency development. First, Planning for teacher competency development at MTs Istiqlal Deli Tua by way of 1). annual planning which is held during madrasah work meetings and direct monitoring from the head of the field. 2). planning at a certain time which is carried out during weekly work meetings with the aim of knowing the constraints felt by teachers so that training for teachers can be held. Second, the application/implementation of teacher competency development at MTs Istiqlal Deli Tua there are 4 teacher competencies which include: 1). Teacher pedagogic competence by participating in seminars, workshops, training both held at school and outside school, 2). Personal competence by providing activities in the form of recitation/consultation for teachers by calling ustadz/resource persons 3). Teacher professional competence by involving teachers in training workshops, seminars and interesting training in accordance with the subject matter taught by the teacher, 4). social competence of teachers with hospitality activities between teachers. Third, evaluation of teacher competency development through weekly evaluations, and academic supervision.